Kill your darlings? Do new aid flows help achieve a poverty minimizing allocation of aid? - Sven Tengstam; Ann-Sofie Isaksson (Research Institute of Industrial Economics (IFN), 2021)
In this study, we derive a poverty-minimizing allocation rule, based on which we assess the povertyefficiency of actual aid allocations, with a special focus on the comparative impact of new donors and new non-aid flows. The results suggest a substantial misallocation of aid. Our benchmark estimates indicate that donors should reallocate nearly half the total aid budget from aid darlings (countries receiving more aid than the allocation rule specifies) to aid orphans (countries receiving less aid than the allocation rule specifies). The estimated poverty-reducing efficiency varies considerably across donors. Whereas new global actors such as the Gates foundation perform well above average, the non-DAC bilateral donors perform clearly worse. Overall, neither the new donors nor the new financial flows alleviate the observed misallocation of aid. While the new donors stand for a non-negligible share of overall poverty reduction, together they perform below average in terms of poverty reduction per aid dollar. Similarly, rather than counteracting the relative neglect of countries identified as particularly underfunded in terms of aid, the non-aid financial flows add to the inequitable distribution. Based on an extensive battery of alternative model calibrations, we establish upper and lower bounds on our estimates, allowing for clear policy recommendations.
Keywords: D63; E61; F35; O11; 330; Aid allocation; Poverty; Donors; Official development assistance; Other official flows